Towards an Ecological Consciousness (American Journal of Islam and Society, 1993)
E. F. Schumacher, the author of Small Is Beautifit said, "We are atwar with Nature and if by chance we win the war, we shall be the loser."This paradox of modem humanity is not universally accepted. However,there is hardly any visible sign of a deceleration in humanity's unilateralwar against the environment. Consequently, humanity is drawing closerand nearer to an imminent debacle.Although "the voices of peace" for solving the crisis could be heardas early as the late 194Os, their mediation has come to be regarded asvaluable only recently. As a result, the global environmental movementhas started shaping the course of developmental strategies. But, unfortunately,the growing concern over environmental devastation is still superficialand not viewed holistically. The ongoing concerns are limited to theextent of the exploitation of natural murces and the sustainability of thedevelopmental processes. However, a few voices that consider the predicamentfrom a holistic viewpoint and in a perspective of "deep ecology"are certainly audible in the global debate. The proponents of the holisticapproach feel that humanity's present awareness of the environmental crisisis not sufficient. What is needed, according to them, is a dispassionateecological consciousness emanating from the synthesis of the completeexperience of humanity since the dawn of civilization and also taking intoconsideration all facets of the ultimate reality.The New Ecological RealismFor quite some time, a relational perspective has been stressed in discussionsabout understanding and solving the ecological crisis. Accordingto this viewpoint, "nature is a web of relations" and therefore "denial ofrelationality is denial of being" (Skolimowski 1991). Furthermore, it expandsthe frontiers of the relationality of the human community to thegreater relationality of all biotic and abiotic members of the biosphere andbeyond. A concept of "the cosmic family" has been envisaged by advocatesof this vision, and humanity is expected to mold its behavior patternsso that human beings can fulfill their obligations towards the vastfamily and honor all relations while deriving benefits from the ~esourcepool of their cultural and physical environments.In its wake, a movement for deep ecology has been proposed. Theterm "deep ecology" signifies the encouragement of a more profound ...